2014
DOI: 10.1007/s00190-014-0763-3
|View full text |Cite
|
Sign up to set email alerts
|

Accounting for Galileo–GPS inter-system biases in precise satellite positioning

Abstract: Availability of two overlapping frequencies L1/E1 and L5/E5a of the signals transmitted by GPS and Galileo systems offers the possibility of tightly combining observations from both systems in a single observational model. A tightly combined observational model assumes a single reference satellite for all observations from both Galileo and GPS systems. However, when inter-system double-differenced observations are created, receiver intersystem bias is introduced. This study presents the results and the methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(86 citation statements)
references
References 19 publications
3
83
0
Order By: Relevance
“…Odijk and Teunissen [13,15] found that the code and phase DISBs between two systems could be cancelled out for baselines with receiver pairs of the same manufacturer. Paziewski and Wielgosz [14] also reached the same conclusion. For receivers of different manufacturers, although DISBs cannot be eliminated, their stability in time has been proven, and thus can be calibrated in advance.…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations
“…Odijk and Teunissen [13,15] found that the code and phase DISBs between two systems could be cancelled out for baselines with receiver pairs of the same manufacturer. Paziewski and Wielgosz [14] also reached the same conclusion. For receivers of different manufacturers, although DISBs cannot be eliminated, their stability in time has been proven, and thus can be calibrated in advance.…”
Section: Introductionsupporting
confidence: 59%
“…Some recent contributions indicated that a priori calibration of DISBs led to better AR and positioning performance [11,[13][14][15]35]. Indeed, between GPS L1-Galileo E1 and other cases with overlapping frequencies, the fractional phase DISB can be easily obtained from fixed integer ambiguities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most recent precise positioning model is developed to be applied in multi-GNSS relative positioning . On the other hand this approach forces additional modelling of hardware biases which are introduced in tightly combined multi-GNSS model (Paziewski and Wielgosz, 2015).…”
Section: Studies On Inter System Bias In Multi-gnss Precise Positioningmentioning
confidence: 99%